Prevalence of bacteria isolated from the lift buttons of two hospitals in Kuantan, Pahang - Muhammad, Izzati; Raja Abd Rahman, Raja Noor Zaliha; Samsuddin, Niza; Kamarudin, Norhidayah; Alias, Norsyuhada (2022)
Background: Lift buttons can be the potential reservoir of pathogenic contaminants. Cleaning routines of public sharing facilities in hospitals including lift buttons have been updated due to the Covid-19 pandemic. These include daily wiping with detergent, weekly disinfection and incident routines. These routines were anticipated to lessen the transmission of pathogens through potential fomites. However, studies regarding lift buttons as fomites in a hospital setting in Malaysia are uncommon. Purpose: The research was conducted to quantify and compare the prevalence of bacteria isolated from the lift buttons between the public hospital (PH) and teaching hospital (TH) in Kuantan, Pahang. Methodology: Sampling using cotton swab was conducted thrice with two weeks intervals (PH: March to April 2021; TH: July to August 2021). The samples (N=100) were processed per standard microbiological procedures. Results: There was no significant difference in the occurrence of bacteria between PB and TH that had the value of 30.4% and 44.4%, respectively. The total bacteria from TH was higher than PH by 1519 CFU/mL (p<0.01). This contrast was contributed by the number of bacteria on the exterior lift buttons of TH. The number of bacteria on the interior lift buttons of both locations did not demonstrate any statistical difference. Both locations were dominated by Gram-positive cocci-shaped bacteria with 68.2% and 89.8% for PH and TH, respectively. The Gram-negative bacteria were only discovered from PH with 11.4% cocci-shaped and 4.5% rod-shaped bacteria. Conclusion: The occurrence of bacteria in both places was tantamount although there was a remarkable difference in the number of bacteria isolated. Further study on the identification of the bacteria colonizing the lift buttons is essential to ensure the efficiency of the decontamination steps used in reducing the prevalence of bacteria.